Inovasi dan Implementasi Diera Digital (International Forum of Researchers and Lecturers, 2026)
Creative technology is the result of the convergence between human creativity and digital innovation that significantly changes the way industries operate. This journal discusses the definition of creative technology, its important role in supporting the development of the digital economy, and the challenges that arise in the implementation process. The research methodology uses a literature study of the latest technological trends, such as artificial intelligence (AI), augmented reality/virtual reality (AR/VR), and digital design. The results of the study show that the integration between technology and creativity is a key factor in increasing competitiveness in the future. Creative technology not only functions as a means of production, but also as a medium of innovation that is able to create added value, expand business opportunities, and encourage digital transformation in various sectors. However, the challenges faced include limited human resources, digital infrastructure readiness, and ethical and regulatory issues. Therefore, creative technology development strategies need to be directed at increasing digital literacy, cross-sector collaboration, and policies that support sustainable innovation.